Spatially regulated mRNA translation enables functional membrane protein integration in synthetic cells - Hang Fu; Lijuan Ma; Chunhua Xu; Jinghua Li; Haochen Ouyang; Congbao Xie; Yunhai Sun; Yuanxiao Tao; Hao Wang; Shuxin Hu; Meifang Fu; Hai Zheng; et al. (Proceedings of the National Academy of Sciences, 2026)
Synthetic cells aim to emulate living systems by reconstituting essential cellular processes within lipid-bound architectures. However, their functional complexity remains constrained by a key challenge: the synthesis and correct integration of hydrophobic membrane proteins via cell-free approaches. Here, inspired by natural cells, we developed a spatially regulated translation strategy in which membrane-anchored mRNAs recruit ribosomes to drive the cotranslational insertion of membrane proteins into lipid bilayers. This design enables efficient in situ synthesis and integration of multiple transmembrane proteins within giant unilamellar vesicles, supporting selective small-molecule transport across membranes. Importantly, the method allows for precise stoichiometric control of membrane protein composition. Together, this work establishes a minimal yet versatile framework for the direct synthesis and integration of membrane proteins, advancing the construction of functional synthetic cells.